Hollow molybdenum disulfide nanosphere as well as preparation method and application thereof

Hollow molybdenum disulfide nanospheres were prepared by solvent-thermal reaction method, and the cyclic stability and electrochemical performance of the positive electrode material of magnesium ion battery were solved by using the Kirkendal effect and layered structure, thus achieving higher magnesium ion diffusion rate and electricity Chemically active sites improve the performance of magnesium ion batteries.

CN119263351APending Publication Date: 2025-01-07HARBIN NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411408117.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When molybdenum disulfide is used as the positive electrode material of magnesium ion batteries, the cycle stability is poor, the discharge specific capacity is low, and the electrochemical performance is poor, which is mainly due to the diffusion kinetic problems caused by the easy generation of impurities and structural instability during the preparation process.

Method used

The hollow molybdenum disulfide nanospheres were prepared by solvent-thermal reaction method. The molybdenum atoms were rapidly diffused to form a cavity structure through the Kirkendal effect, and vulcanized at relatively low temperatures to form an expanded structure and 1T phase to improve electrochemical performance. .

Benefits of technology

It improves the diffusion rate and cyclic stability of magnesium ions, increases the electrochemical active site, and improves the performance of magnesium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263351A_ABST
    Figure CN119263351A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of magnesium ion battery positive electrode materials, and discloses a hollow molybdenum disulfide nanosphere and a preparation method and application thereof. The preparation method comprises the following steps that molybdenum glycerate is used as a precursor, molybdenum glycerate and a sulfur source are dispersed in a first dispersing agent, a vulcanization reaction is conducted through solvothermal, molybdenum atoms in molybdenum glycerate are diffused outwards in the vulcanization process through the Kirkendall effect, sulfur atoms form vacancies in molybdenum glycerate, the vacancies are gradually accumulated and combined to form a cavity, and molybdenum glycerate is obtained; the hollow molybdenum disulfide nano material is obtained. By regulating and controlling the vulcanization time and temperature in the vulcanization process, the space structure and surface appearance of the molybdenum disulfide sphere are regulated and controlled to synthesize the hollow molybdenum disulfide nanosphere with the expanded layer structure, and the 1T phase structure of molybdenum disulfide is regulated and controlled. Through the synergistic effect among the 1T phase structure, the hollow structure and the expanded layer structure, the ion utilization rate and the specific discharge capacity in the magnesium ion battery are improved, so that the cycling stability and the electrochemical performance of the magnesium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnesium ion battery positive electrode materials, and specifically relates to a hollow molybdenum disulfide nanosphere and a preparation method and application thereof. Background Art

[0002] Magnesium-ion battery is a new type of battery with great potential. Compared with lithium, magnesium is a more ideal metal positive electrode. However, at this stage, the low electrochemical activity of magnesium-ion batteries, corrosion of the metal magnesium negative electrode, and serious solvation phenomena have hindered their industrial development. Therefore, it is necessary to develop suitable positive electrode materials. Researchers in this field have been working hard to explore new magnesium-ion battery positive electrode materials with excellent performance. As a magnesium-ion battery positive electrode material, it must have the following characteristics: high energy density, good cycle stability, good safety, and good reversible deintercalation and insertion ability of magnesium ions.

[0003] At present, the research on positive electrode materials of magnesium ion batteries mainly focuses on transition metal sulfides, transition metal oxides, polyanionic compounds, sulfur and chalcogenide compounds, organic matter and composite materials. Transition metal oxides, as positive electrode materials for magnesium ion batteries, are assembled into batteries that not only have a high discharge capacity, but also have good cycle performance. However, Mg 2+ The diffusion rate in this positive electrode material is very slow; while transition metal borides are used as positive electrode materials for lithium-ion batteries, Mg 2+ The rate of insertion into the cathode material is much lower than that of Li + The insertion rate of polyanion compounds was found through research. The polyanion positive electrode material with olivine structure can not only realize the reversible insertion and extraction of a large number of ions, but also control the discharge voltage. However, its electrical conductivity is poor, which will greatly reduce the discharge performance of the battery.

[0004] Most of the published high-performance magnesium-ion battery cathode materials are insertion-extraction materials. This is because different types of electrolytes will react with Mg 2+ Ion combination produces different types of carriers, which affects the reaction mechanism of the positive electrode. The embedding kinetics of magnesium ions essentially depends on their diffusion barrier and mobility in the material, and the diffusion barrier and ion mobility are closely related to the crystal structure of the material. In addition, most high-performance magnesium ion battery positive electrode materials have a two-dimensional layered structure. For example, the van der Waals interaction between the double layers of molybdenum disulfide is much weaker than the Mo-S bond in the single layer, so it is easy to be peeled off under the action of external force to form a dispersed single layer molecule, which solves the problem of Mg 2+ After entering the positive electrode material, a strong Coulomb force interaction is generated between it and the positive electrode material, resulting in slow diffusion kinetics, which leads to the problem of poor magnesium storage performance of most positive electrode materials. Therefore, two-dimensional layered material magnesium ion battery positive electrode material can significantly improve the performance of magnesium ion batteries.

[0005] Transition metal sulfide is a typical embedding / de-embedding matrix material. When used as a positive electrode material, it has advantages such as good reversibility, high operating voltage and higher discharge specific capacity, and is considered to be a promising positive electrode material for magnesium ion batteries. Among them, molybdenum disulfide has attracted widespread attention from researchers due to its unique layered structure and good structural stability, which can provide a two-dimensional transmission channel for the diffusion of embedded ions. The methods for preparing molybdenum disulfide as a positive electrode material in the prior art mainly include solid phase synthesis, sol-gel method and vapor deposition method. The solid phase synthesis method requires a high reaction temperature, high energy consumption, and easy formation of impurities during the reaction; the sol-gel method is complex in the process of preparing molybdenum disulfide, and the heat treatment step may cause material agglomeration. The vapor deposition method requires expensive equipment to prepare molybdenum disulfide, with a complex process and low yield.

[0006] Therefore, since impurities are easily generated in the process of preparing molybdenum disulfide in the prior art, the prepared molybdenum disulfide is impure, which leads to poor cycle stability, low discharge specific capacity and poor electrochemical performance of magnesium ion batteries when molybdenum disulfide is used as the positive electrode material. Summary of the invention

[0007] In order to solve the problems of poor cycle stability, low discharge specific capacity and poor electrochemical performance of magnesium ion batteries when molybdenum disulfide is used as the positive electrode material. The present invention provides a hollow molybdenum disulfide nanosphere and its preparation method and application. The present invention is prepared using safe and readily available raw materials, and the preparation method is simple. The present invention uses glycerol as a reducing agent, disperses a molybdenum source and glycerol in a second dispersant in sequence, adopts a solvothermal reaction to synthesize spherical molybdenum glycerate, and obtains a spherical structure of molybdenum glycerate by regulating the reaction temperature and reaction time of molybdenum glycerate; on the basis of the spherical structure of molybdenum glycerate, a unique hollow nanosphere structure with an expanded layer structure is constructed, spherical molybdenum glycerate is used as a precursor, molybdenum glycerate and a sulfur source are dispersed in a first dispersant in sequence, and a solvothermal reaction is adopted. By regulating the vulcanization time of the vulcanization reaction, the molybdenum element inside the molybdenum glycerate during the vulcanization process is continuously diffused outward, and through the Kirkendall effect, the molybdenum atoms diffuse outward rapidly, and the sulfur atoms diffuse at a slower rate and form inside the nanoparticles. Vacancies, the gradual accumulation and merger of vacancies form cavities, thereby forming defects inside the sphere, and hollow MoS2 nanospheres are prepared; at the same time, by regulating the sulfurization temperature during the sulfurization reaction and maintaining it at a relatively low temperature, the sulfurization is incomplete, thereby forming residual Mo oxides. During the sulfurization process, molecules or ions in the solution may be captured and embedded in the MoS2 interlayers, resulting in the expansion of the MoS2 interlayer spacing to obtain an extended layer structure; in addition, during the sulfurization process, due to the lattice expansion of MoS2, a partial transformation from 2H phase to 1T phase structure is achieved. The electrochemical performance is improved through the introduction of a partial 1T phase structure and the synergistic effect of the hollow nanosphere structure with an extended layer structure.

[0008] The first object of the present invention is to provide a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0009] Spherical molybdenum glycerate is used as a precursor, molybdenum glycerate and a sulfur source are dispersed in a first dispersant in sequence, and a solvent thermal method is used to carry out a sulfurization reaction. Through the Kirkendall effect, the molybdenum atoms inside the molybdenum glycerate diffuse outward during the sulfurization process, and the sulfur atoms form vacancies inside the molybdenum glycerate, which gradually accumulate and merge to form cavities, thereby synthesizing hollow molybdenum disulfide nanomaterials.

[0010] It should be noted that in a preferred embodiment of the present invention, the sulfur source is one or more of sodium sulfide nonahydrate, thioacetamide and thiourea. Sodium sulfide nonahydrate is a better reducing agent. Molybdenum disulfide is formed by reacting molybdenum glycerate with sodium sulfide nonahydrate in a dispersant. At the same time, during the sulfurization process of the solvent thermal reaction, the molybdenum atoms diffuse rapidly outward through the Kirkendall effect, and the sulfur atoms diffuse at a slower rate and form vacancies inside the nanoparticles. The vacancies gradually accumulate and merge to form cavities. In a preferred embodiment of the present invention, the mass ratio of molybdenum glycerate to the sulfur source is 8:12 to 10:30, and the dosage ratio of the sulfur source to the first dispersant is 1 mg to 3 mg: 3 mL to 6 mL.

[0011] Since the curing time and curing temperature of molybdenum disulfide during the curing reaction process play a key role in the formation of hollow structure and expanded layer structure, when the curing time is insufficient, the internal molybdenum element is not completely cured, and there is still a solid structure inside; when the curing time is appropriate, a hollow structure is formed and completely cured; when the curing time is too long, it may be because the internal molybdenum atoms have all diffused outward to form a hollow structure, and there is no substance in the structure that can exchange and diffuse with sulfur atoms, and the hollow sphere is relatively fragile without material support, and the sulfur atoms hit the sphere and cause the sphere to break. In addition, the relatively low temperature leads to incomplete curing, thereby forming residual molybdenum oxide. During the curing process, molecules or ions in the solution may be captured and embedded in the molybdenum disulfide interlayer, resulting in the expansion of the interlayer spacing of molybdenum disulfide. In a preferred embodiment of the present invention, the curing temperature is 180°C to 190°C, and the curing time is 6h to 6.5h.

[0012] Furthermore, after the solvothermal reaction is completed, the mixture is cooled to room temperature, washed, centrifuged, and dried to obtain molybdenum disulfide powder. The solid-liquid separation is better achieved by washing and centrifugation to separate the molybdenum disulfide powder from the solvent. The solvents for washing and centrifugation are water and ethanol, and water is used to reduce impurity ions, and ethanol is used to control the agglomeration of molybdenum disulfide particles. In a preferred embodiment of the present invention, the centrifuge speed of the molybdenum disulfide is 8000rpm to 10000rpm, and the centrifugation time is 5min. Furthermore, water molecules are removed by oven drying. In a preferred embodiment of the present invention, the drying temperature of the molybdenum glycerate is 40℃ to 60℃, and the drying time is 12h to 24h.

[0013] In a preferred embodiment of the present invention, the platinum glycerate is prepared by the following steps:

[0014] Glycerol is used as a reducing agent, a molybdenum source and glycerol are sequentially dispersed in a second dispersant to obtain a molybdenum glycerate solution, and a solvothermal reaction is used to synthesize spherical molybdenum glycerate.

[0015] It should be noted that in a preferred embodiment of the present invention, the molybdenum source is molybdenum pentachloride or ammonium molybdate. Molybdenum pentachloride as a molybdenum source can effectively promote the reaction, improve the purity of the product, and provide molybdenum ions in the structure of molybdenum disulfide nanomaterials. In the molybdenum glycerate solution, glycerol releases hydrogen ions and reacts with the molybdenum ions in molybdenum pentachloride to generate a reduction product, molybdenum glycerate. In a preferred embodiment of the present invention, the second dispersant is isopropanol. As a solvent, isopropanol can be freely mixed with water and has a stronger solubility for lipophilic substances than ethanol. The ions in molybdenum pentachloride and glycerol are composed of Mo 5+ Connect, Mo 5+ Less prone to forming a spherical structure, in a preferred embodiment of the present invention, the molybdenum pentachloride and glycerol usage ratio is 6mg-20mg: 1.5mL-1.9mL, and the volume ratio of glycerol to isopropanol is 1.5-1.9: 4-5. In order to make molybdenum pentachloride and glycerol completely dissolved in isopropanol to form a uniformly mixed molybdenum glycerate solution, the present invention adopts a stirring method. In a preferred embodiment, the stirring time is 20min-40min, and the stirring rate is 500rpm-1000rpm.

[0016] Since the reaction temperature and reaction time of molybdenum glycerate in the solvothermal reaction play a key role in the formation of the spherical structure of molybdenum glycerate, when the temperature is low or the reaction time is short, it is difficult for molybdenum glycerate to form a spherical structure; when the temperature is too high or the reaction time is too long, the spherical structure may be broken. In a preferred embodiment of the present invention, the temperature of the solvothermal reaction is 200°C to 210°C, and the time is 3h to 3.5h.

[0017] Furthermore, after the solvothermal reaction is completed, solid-liquid separation is better achieved by washing centrifugation to separate the molybdenum glycerate powder from the solvent. The solvents for washing centrifugation are water and ethanol, and water is used to reduce impurity ions, and ethanol is used to control the agglomeration of molybdenum glycerate particles. In a preferred embodiment of the present invention, the centrifuge speed of the molybdenum glycerate is 8000rpm~10000rpm, and the centrifugation time is 5min. Furthermore, water molecules are removed by oven drying. In a preferred embodiment of the present invention, the drying temperature of the molybdenum glycerate is 40℃~60℃, and the drying time is 12h~24h.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] In the process of preparing hollow molybdenum disulfide nanospheres, the present invention uses spherical molybdenum glycerate as a precursor, disperses molybdenum glycerate and a sulfur source in a first dispersant in sequence, and uses a solvent thermal method to perform a sulfurization reaction. During the sulfurization process, the Kirkendall effect is used to rapidly diffuse the molybdenum atoms inside the molybdenum glycerate outward, and the sulfur atoms diffuse at a slower rate and form vacancies inside the molybdenum glycerate nanoparticles. As the vacancies gradually accumulate and merge to form cavities, defects are formed inside the sphere, and finally a molybdenum disulfide nanomaterial with a hollow structure is obtained. In addition, due to the relatively low temperature, the sulfurization is incomplete, thereby forming residual molybdenum oxide. During the sulfurization process, molecules or ions in the molybdenum disulfide solution may be captured and embedded in the molybdenum disulfide interlayer, resulting in an expansion of the molybdenum disulfide interlayer spacing. The expansion of the molybdenum disulfide interlayer spacing can increase the Mg 2+ and S 2- The distance of action weakens the electrostatic force between the two, thereby reducing Mg 2+ The diffusion energy barrier between layers reduces the transmission distance of magnesium ions, showing better rate performance. In addition, due to the large interlayer spacing, the interlayer interaction is reduced during the magnesium ion embedding / de-embedding process, which can alleviate the volume change caused by "lattice breathing", thereby improving the structural stability and showing good cycle reversibility.

[0020] In the process of preparing hollow molybdenum disulfide nanospheres, the molybdenum disulfide undergoes lattice expansion during the sulfurization process, achieving a partial transformation from the 2H phase to the 1T phase structure, thereby preparing a molybdenum disulfide nanomaterial with a 1T phase structure. Ordinary 2H phase molybdenum disulfide is a triangular prism structure with semiconductor properties, while the 1T phase is an octahedral structure with metallic conductor properties, and its conductivity is 107 times higher than that of the 2H phase. Therefore, the 1T phase molybdenum disulfide exhibits faster electron and charge injection / transfer, has extraordinary electronic conductivity and more electrochemical active sites.

[0021] In the process of preparing hollow molybdenum disulfide nanospheres, the present invention constructs a unique hollow nanosphere structure and an expanded layer structure based on the molybdenum glycerate spherical structure, and introduces a part of the 1T phase into the 2H phase structure. Through the introduction of the 1T phase structure and the synergistic effect of the hollow nanospheres with the expanded layer structure, the contact area of ​​the magnesium ions is increased, the hollow nanospheres have abundant defects and thus provide more active sites, thereby effectively improving the utilization rate of ions in the magnesium ion battery and the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The projection electron microscope photos of molybdenum glycerate at different vulcanization times of the present invention and the vulcanization process diagram of molybdenum glycerate are shown in the figures. In each figure, Figure a is unvulcanized, Figure b is vulcanized for 3h, Figure c is vulcanized for 6h, Figure d is vulcanized for 10h, and Figure e is a vulcanization process diagram of molybdenum glycerate.

[0023] Figure 2 Scanning electron microscope photographs and projection electron microscope photographs of Examples 1 and 4 of the present invention. In each figure, Figure a is a scanning electron microscope photograph of Example 1, Figure b is a projection electron microscope photograph of Example 1, Figure c is a scanning electron microscope photograph of Comparative Example 1, and Figure d is a projection electron microscope photograph of Comparative Example 1.

[0024] Figure 3 The X-ray diffraction diagram, X-ray photoelectron spectrum diagram and Raman spectrum diagram of Example 1 of the present invention are shown in Figure a, Figure b is a high-resolution spectrum diagram of Mo3d, Figure c is a high-resolution spectrum diagram of S2p, and Figure d is a Raman spectrum diagram.

[0025] Figure 4 1 is a small current and rate curve of Example 1 of the present invention. In each figure, Figure a is a small current curve and Figure b is a rate curve. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand that the technical solution of the present invention can be implemented, the present invention is further described below in conjunction with specific embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.

[0028] The invention is further described below through specific examples.

[0029] Example 1

[0030] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0031] 200 mg of molybdenum pentachloride and 19 mL of glycerol were added to 50 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride was completely dissolved to obtain a uniformly mixed molybdenum glycerate solution. The molybdenum glycerate solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C and kept warm for 3 h. After the molybdenum glycerate solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain molybdenum glycerate powder. Weigh 120 mg of molybdenum glycerate powder and 300 mg of sodium sulfide nonahydrate respectively, add them to 60 mL of anhydrous ethanol in turn, stir at a stirring rate of 500 rpm for 45 min until mixed evenly to obtain a uniformly dispersed mixed solution, transfer the mixed solution to a 100 mL reactor, put it in an oven, heat it to 180 ° C and keep it warm for 6 h, after the mixed solution is cooled to room temperature, wash and centrifuge it with water and ethanol 5 times, the centrifuge speed is 8000 rpm, the centrifugation time is 5 min, and then put it in an oven at 40 ° C for 12 h, and dry it to obtain dark brown hollow molybdenum disulfide powder, hollow molybdenum disulfide, referred to as EH-MoS2 in English,

[0032] Example 2

[0033] The present embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps: 200 mg of molybdenum pentachloride and 19 mL of glycerol are sequentially added to 50 mL of isopropanol, stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride is completely dissolved to obtain a uniformly mixed molybdenum glycerate solution, the molybdenum glycerate solution is transferred to a 100 mL reactor, and placed in an oven, heated to 200° C. and kept warm for 3 h, after the molybdenum glycerate solution is cooled to room temperature, washed and centrifuged with water and ethanol for 5 times, the centrifuge speed is 8000 rpm, the centrifugation time is 5 min, and then placed in an oven at 60° C. and kept warm for 12 h , and dry to obtain molybdenum glycerate powder; weigh 120 mg of molybdenum glycerate powder and 300 mg of sodium sulfide nonahydrate respectively, add them into 60 mL of anhydrous ethanol in turn, stir at a stirring rate of 500 rpm for 45 min, until mixed evenly, to obtain a uniformly dispersed mixed solution, transfer the mixed solution to a 100 mL reactor, and put it into an oven, heat it to 180 ° C and keep it warm for 3 h. After the mixed solution is cooled to room temperature, wash and centrifuge it 5 times with water and ethanol, the centrifuge speed is 8000 rpm, the centrifugation time is 5 min, and then put it into an oven at 40 ° C for 12 h, and dry it to obtain dark brown EH-MoS2 powder.

[0034] Example 3

[0035] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0036] 200 mg of molybdenum pentachloride and 19 mL of glycerol were added to 50 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride was completely dissolved to obtain a uniformly mixed molybdenum glycerate solution. The molybdenum glycerate solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C for 3 h, and after the molybdenum glycerate solution was cooled to room temperature, it was washed and centrifuged with water and ethanol for 5 times, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain molybdenum glycerate powder; respectively Take 120 mg of molybdenum glycerate powder and 300 mg of sodium sulfide nonahydrate, add them to 60 mL of anhydrous ethanol in sequence, stir at a stirring rate of 500 rpm for 45 minutes, until mixed evenly, to obtain a uniformly dispersed mixed solution; transfer the mixed solution to a 100 mL reactor, put it into an oven, heat it to 180 ° C and keep it warm for 10 hours, after the mixed solution is cooled to room temperature, wash and centrifuge it with water and ethanol for 5 times, the centrifuge speed is 8000 rpm, the centrifugation time is 5 minutes, then put it into an oven at 40 ° C for 12 hours, and dry it to obtain dark brown EH-MoS2 powder.

[0037] Example 4

[0038] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0039] 250 mg of ammonium molybdate and 19 mL of glycerol were added to 50 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride was completely dissolved to obtain a uniformly mixed molybdenum glycerate solution. The molybdenum glycerate solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C for 3 h, and after the molybdenum glycerate solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain molybdenum glycerate powder; Weigh 120 mg of molybdenum glycerate powder and 300 mg of sodium sulfide nonahydrate were added to 60 mL of anhydrous ethanol in sequence, and stirred at a stirring rate of 500 rpm for 45 min until mixed evenly to obtain a uniformly dispersed mixed solution. The mixed solution was transferred to a 100 mL reactor and placed in an oven, heated to 180 ° C and kept warm for 6 h. After the mixed solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol at a centrifuge speed of 8000 rpm for 5 min. It was then placed in an oven at 40 ° C for 12 h and dried to obtain dark brown EH-MoS2 powder.

[0040] Example 5

[0041] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0042] 200 mg of platinum pentachloride and 30 mL of glycerol were added to 60 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the platinum pentachloride was completely dissolved to obtain a uniformly mixed glycerate molybdenum solution, and the glycerate molybdenum solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C and kept warm for 3 h. After the glycerate molybdenum solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain glycerate molybdenum powder; Weigh 120 mg of molybdenum glycerate powder and 300 mg of thiourea, add them to 60 mL of anhydrous ethanol in sequence, stir at a stirring rate of 500 rpm for 45 min, until mixed evenly to obtain a uniformly dispersed mixed solution, transfer the mixed solution to a 100 mL reactor, put it into an oven, heat it to 180 ° C and keep it warm for 6 h. After the mixed solution is cooled to room temperature, wash and centrifuge it with water and ethanol for 5 times, the centrifuge speed is 8000 rpm, the centrifugation time is 5 min, then put it into an oven at 40 ° C for 12 h, and dry it to obtain dark brown EH-MoS2 powder.

[0043] Example 6

[0044] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0045] 200 mg of molybdenum pentachloride and 19 mL of glycerol were added to 50 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride was completely dissolved to obtain a uniformly mixed molybdenum glycerate solution. The molybdenum glycerate solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C for 3 h, and after the molybdenum glycerate solution was cooled to room temperature, it was washed and centrifuged with water and ethanol for 5 times, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain molybdenum glycerate powder; respectively Take 120 mg of molybdenum glycerate powder and 500 mg of thioacetamide, add them to 60 mL of anhydrous ethanol in sequence, stir at a stirring rate of 500 rpm for 45 minutes, until mixed evenly, to obtain a uniformly dispersed mixed solution, transfer the mixed solution to a 100 mL reactor, and put it into an oven, heat it to 180 ° C and keep it warm for 6 hours. After the mixed solution is cooled to room temperature, wash and centrifuge it with water and ethanol for 5 times, the centrifuge speed is 8000 rpm, the centrifugation time is 5 minutes, and then put it into an oven at 40 ° C for 12 hours, and dry it to obtain dark brown EH-MoS2 powder.

[0046] Comparative Example 1

[0047] This embodiment provides a method for preparing hollow molybdenum disulfide nanospheres, comprising the following steps:

[0048] 200 mg of molybdenum pentachloride and 19 mL of glycerol were added to 50 mL of isopropanol in sequence, and stirred at a stirring rate of 500 rpm for 20 min until the molybdenum pentachloride was completely dissolved to obtain a uniformly mixed molybdenum glycerate solution. The molybdenum glycerate solution was transferred to a 100 mL reactor and placed in an oven, heated to 200 ° C and kept warm for 3 h. After the molybdenum glycerate solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol, the centrifuge speed was 8000 rpm, the centrifugation time was 5 min, and then placed in an oven at 60 ° C for 12 h, and dried to obtain molybdenum glycerate powder; 120 mg of molybdenum glycerate and 300 mg of sodium sulfide nonahydrate were weighed respectively, and added to 60 mL of The mixture was stirred in anhydrous ethanol at a stirring rate of 500 rpm for 45 min until it was evenly mixed to obtain a uniformly dispersed mixed solution. The mixed solution was transferred to a 100 mL reactor and placed in an oven, heated to 180 ° C for 6 h. After the solution was cooled to room temperature, it was washed and centrifuged 5 times with water and ethanol. The centrifuge speed was 8000 rpm and the centrifugation time was 5 min. The mixture was placed in an oven at 40 ° C for 12 h and dried to obtain dark brown EH-MoS2 powder. The EH-molybdenum disulfide powder was placed in a crucible and then placed in a tubular furnace. The temperature was raised to 500 ° C at a rate of 1 ° C / min under hydrogen and argon mixed gas conditions and heat treated for 2 h to obtain annealed EH-MoS2 powder.

[0049] Figure 1 The projection electron microscope (Figure ad) photos of molybdenum glycerate at different curing times of the present invention and the sulfurization process diagram of molybdenum glycerate (Figure e) are shown. The experiment first synthesized a molybdenum glycerate precursor, and by controlling the curing time, the preparation of the hollow structure of molybdenum disulfide was achieved. As shown in Figure a, molybdenum glycerate appears as a smooth solid sphere; as shown in Figure b, after 3 hours of curing in Example 2, a sphere with a partially solid interior and a sheet growing outside is formed; as shown in Figure c, after 6 hours of curing in Example 1, a hollow spherical structure is formed; as shown in Figure d, when the curing time is increased to 10 hours, the EH-MoS2 sphere formed in Example 3 has a hollow structure. The spatial structure of the EH-MoS2 sphere formed at different curing times is different. The formation of the hollow spherical structure utilizes the Kirkendall effect to rapidly diffuse molybdenum atoms outward, and sulfur atoms form vacancies at a slower diffusion rate and inside the nanoparticles. The gradual accumulation and merging of vacancies form cavities, thereby forming defects inside the sphere, and finally obtaining a hollow structure. Figure e is a schematic diagram of the vulcanization process, from which it can be seen that the hollow structure is formed during vulcanization, indicating that the present invention can prepare a hollow molybdenum disulfide nano-spherical structure based on the molybdenum glycerate spherical structure by regulating the vulcanization time.

[0050] Figure 2The scanning electron microscope photos (Figures a and c) and projection electron microscope photos (Figures b and d) of Example 1 of the present invention and Comparative Example 1. As can be seen from Figure a, EH-MoS2 is different from the smooth sphere of molybdenum glycerate. EH-MoS2 is a highly uniform sphere with a radius of 370nm with a lamellar structure. As can be seen from Figure b, the interlayer spacing on the (002) crystal plane of EH-MoS2 is 0.727nm. As can be seen from Figure c, the morphology of EH-MoS2 prepared in Example 1 is similar to that of EH-MoS2 prepared in Comparative Example 1. As can be seen from Figure d, the interlayer spacing on the (002) crystal plane of EH-MoS2 prepared in Comparative Example 1 is 0.625nm. Obviously, the interlayer spacing of EH-MoS2 prepared in Example 1 is much larger than the interlayer spacing of EH-MoS2 prepared in Comparative Example 1 after annealing, indicating that the present invention can prepare hollow molybdenum disulfide nanospheres with an expanded layer structure by controlling the sulfurization temperature during the sulfurization process.

[0051] Figure 3 The X-ray diffraction diagram (Figure a), X-ray photoelectron energy spectrum diagram (Figure bc) and Raman spectrum diagram (Figure d) of Example 1 of the present invention. As shown in Figure a, diffraction peaks appear at 2θ=32.68°, 39.53° and 58.33°, which correspond to the (002) crystal plane when compared with the standard hexagonal molybdenum disulfide card (JCPDS No.37-1492), which is consistent with the results of TEM, indicating that the present application has prepared EH-MoS2 with a 1T phase octahedral structure. As shown in Figure b, it is a high-resolution spectrum of Mo3d, and the two peaks at the binding energy of 228.9eV and 232.0eV correspond to the 1T phase Mo3d 3 / 2 and Mo3d 5 / 2 orbital, the binding energy is located at 228.9eV and 232.0eV, the two peaks correspond to 2H phase Mo3d 3 / 2 and Mo3d 5 / 2 orbital; the two peaks at 233.3eV and 236eV correspond to Mo-O. From the high-resolution spectrum of S2p (Figure c), it can be seen that the two peaks at 161.3eV and 162.6eV correspond to 1T phase S2p 1 / 2 and S2p 3 / 2 orbital, the binding energy is located at 162.1eV and 163.6eV, the two peaks correspond to the 2H phase S2p 1 / 2 and S2p 3 / 2 The trajectory shows that the EH-MoS2 prepared in Example 1 has obvious 1T phase, 2H phase and Mo-O bond, which indicates that the present invention can prepare molybdenum disulfide nanomaterials with 1T phase structure by regulating the sulfurization time and sulfurization temperature.

[0052] As shown in Figure d, the spectrum of the EH-MoS2 sample is located at 386 and 412 cm-1 The characteristic peaks appear, corresponding to the in-plane E 1 2g and outer surface A 1g vibration mode, and three peaks appeared in the spectrum, located at 207.5cm -1 、231.9cm -1 and 363.2cm -1 Wavenumber band. By searching the literature, it was proved that these three new peaks correspond to Mo-O bonds, which further proved the doping of oxygen. During the sulfurization process, the relatively low temperature leads to incomplete sulfurization, resulting in the formation of residual molybdenum oxide. During the sulfurization process, molecules or ions in the solution may be captured and embedded in the MoS2 interlayer, resulting in the expansion of the MoS2 interlayer spacing.

[0053] Therefore, the present invention controls the vulcanization time and the vulcanization temperature during the vulcanization process to prepare molybdenum disulfide hollow nanospheres with an expanded layer structure based on the molybdenum glycerate spherical structure. At the same time, a partial 1T phase is introduced into the 2H phase structure. The electrochemical performance of molybdenum disulfide as a positive electrode material for magnesium ion batteries is further improved through the introduction of the partial 1T phase structure and the synergistic effect of the molybdenum disulfide hollow nanosphere structure with an expanded layer structure.

[0054] Low current test and rate performance test

[0055] The hollow molybdenum disulfide nanomaterials prepared in Example 1 and Comparative Example 1 were used as positive electrode materials for magnesium ion batteries to conduct low current tests and rate performance tests. The test process is as follows:

[0056] The low current test used cyclic voltammetry to study the storage mechanism of magnesium ions. -1 The reversible capacity of the battery is obtained after 200 cycles at a current of 20-1000 mA·g -1 The test was carried out at a current density of .

[0057] Figure 4 The low current (Figure a) and rate curve (Figure b) of Example 1 of the present invention are shown in Figure a. As shown in Figure a, the EH-MoS2 prepared in Example 1 has a current of 20 mA·g -1 The reversible capacity after 200 cycles at a current of 331.3 mAh g -1 This indicates that the expansion of the interlayer spacing of MoS2 is important for increasing the active sites and improving the Mg 2+ The diffusion rate has a significant promoting effect, solving the problem of Mg 2+ The problem of slow ion diffusion during the extraction / insertion process. As shown in Figure a, at 20, 50, 100, 200, 500 and 1000 mA g -1At current densities of 1.3, 1.5, 2.1, 3.5, 4.7, 5.9, and 1.1 mAh g−1, the discharge capacities of EH-MoS2 are 366.5, 311, 264.2, 229.8, 187.9, and 150.7 mAh g−1, respectively. -1 , proving that the expansion of interlayer spacing increases the ion diffusion rate and solves the problem of Mg 2+ The problem of slow ion diffusion during the extraction / intercalation process.

[0058] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing hollow molybdenum disulfide nanospheres, characterized in that: include: Spherical molybdenum glycerate is used as a precursor, molybdenum glycerate and a sulfur source are dispersed in a first dispersant in sequence, and a solvent thermal method is used to carry out a sulfurization reaction. Through the Kirkendall effect, the molybdenum atoms inside the molybdenum glycerate diffuse outward during the sulfurization process, and the sulfur atoms form vacancies inside the molybdenum glycerate, which gradually accumulate and merge to form cavities, thereby synthesizing hollow molybdenum disulfide nanomaterials.

2. The method for preparing hollow molybdenum disulfide nanospheres according to claim 1, characterized in that: The temperature of the vulcanization reaction is 180° C. to 190° C., and the time is 6 h to 6.5 h.

3. The method for preparing hollow molybdenum disulfide nanospheres according to claim 1, characterized in that: The mass ratio of the molybdenum glycerate to the sulfur source is 8-12:10-30.

4. The method for preparing hollow molybdenum disulfide nanospheres according to claim 1, characterized in that: The usage ratio of the sulfur source to the first dispersant is 1 mg to 3 mg: 3 mL to 6 mL.

5. The method for preparing hollow molybdenum disulfide nanospheres according to claim 1, characterized in that: The platinum glycerate is prepared by the following steps: Glycerol is used as a reducing agent, a molybdenum source and glycerol are sequentially dispersed in a second dispersant, and a solvent thermal reaction is adopted to synthesize spherical molybdenum glycerate.

6. The method for preparing hollow molybdenum disulfide nanospheres according to claim 5, characterized in that: The temperature of the solvent thermal reaction is 200° C. to 210° C., and the time is 3 h to 3.5 h.

7. The method for preparing hollow molybdenum disulfide nanospheres according to claim 5, characterized in that: The usage ratio of the molybdenum source and glycerol is 6mg-20mg:1.5mL-1.9mL.

8. The method for preparing hollow molybdenum disulfide nanospheres according to claim 5, characterized in that: The volume ratio of the glycerol to the second dispersant is 1.5-1.9:4-5.

9. Hollow molybdenum disulfide nanospheres prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the hollow molybdenum disulfide nanospheres according to claim 9 in positive electrode materials of magnesium ion batteries.